Acute pancreatitis mimicking myocardial ischemia: A case report and a review of the literature - Antonio Villa; Francesca Campagna; Giulia Gallotta; Riccardo Bennicelli; Paola Sartori (Journal of Health and Social Sciences)
In literature, acute pancreatitis has been shown to be associated with a wide range of electrocardiographic changes. In the present report, we describe a case of a young woman who presented to our emergency room with chest pain and electrocardiographic alterations suggestive of myocardial ischemia; laboratory data showed elevated amylase and lipase levels. A computed tomography (CT) scan of the abdomen confirmed the diagnosis of acute pancreatitis. In the next day, she repeated the electrocardiogram, which showed a regression of the ST-segment depression. T-waves changes and ST-segment depression are common in acute pancreatitis and, therefore, emergency physicians should consider acute pancreatitis in the differential diagnosis of patients presenting with chest pain and electrocardiographic changes.